Arquivo, repertorio e escrevivência: possibilidades entre performance e a poesia de Conceição Evaristo - Oliveira, Janaina Falcão de (2023)
This research aims to search the links between literature, performance and its possibilities. This research understands performance as an epistemology, basing itself in Diana Taylor’s writings about America’s cultural memory and its relation between archive and repertory. This research follows a decolonial approach that questions colonial culture and overlapping knowledge about narratives in a way that it opens possibilities for visibility and knowledge appreciation. Conceição Evaristo, using literature, opens the possibility to social transformation and production of knowledge in a way that appreciates ethics and black culture aesthetics. The book Poemas da Recordação e outros Movimentos builds a repertoire about writing-livings that is powerful and a space of body experienc appreciation. The book values the exchanges between poems and performances as a valuable and fertile terrain of representation possibilities.